Inferring microevolutionary patterns from allele-size frequency distributions of minisatellite loci: a worldwide study of the APOB 3' hypervariable region polymorphism. - Destro-Bisol, G; Capelli, C; Belledi, M (2000)
The availability of numerous population and molecular data makes the apolipoprotein B 3' hypervariable region (APOB 3' HVR) polymorphism ideal for a pilot study of the relationships between the allele-size frequency distributions (referred to as allele-size distributions) of minisatellite loci and the microevolutionary processes underlying their present-day polymorphism in human populations. In this paper, we present a worldwide APOB 3' HVR study, based on published and unpublished data, which refers to 36 populations. We systematically compare APOB 3' HVR within-group diversity (in terms of heterozygosity, number of alleles, and allele-size variance) in numerous human populations, including African, European, Asian, Amerindian, Australomelanesian, and Polynesian groups. Overall, our analyses indicate a greater APOB 3' HVR diversity in Africans than non-Africans. Then, we compare APOB 3' HVR allele-size distributions. The APOB 3' HVR allele-size distribution is found to be quasi-unimodal in Africans and bimodal or nonunimodal in non-African populations. The analysis of the distribution of pairwise comparisons suggests that Africans expanded earlier and/or that their ancestral population was larger than other continental groups. As a final step, we examine APOB 3' HVR interpopulational relationships by using three genetic distances. The F(ST) genetic distance, which assumes genetic drift as being the agent that differentiates populations, provides results that are more congruent with established anthropological knowledge than mutation-based distances (D(SW) and R(ST)). We hypothesize that the ancestral population was characterized by a high heterozygosity, an extended range of allele size, and a quasi-unimodal allele-size distribution centered on allele *37, features persisting in examined African populations. Sampling processes during "out-of-Africa" migrations would be responsible for the decrease in APOB 3' HVR gene diversity and the nonunimodal allele-size distribution observed in non-Africans. Some possible confounding factors are discussed and a prospect of how the hypothesis could be refined and tested is given.